analisis butir soal Analisis Kualitas Butir Soal Akuntansi Perusahaan Jasa, Dagang, Dan Manufaktur Menggunakan Aplikasi Anates Terhadap Siswa-Siswi SMK/MAK - Arlindianie, Najwa Khania; A’isyah, Evi Trinur; Rahmah, Elsa Afsari; Hakim, Luqman; Pratiwi, Vivi (Nirta Learning Centre, 2024)
This research contributes to the development of assessment tools for accounting subjects. By analyzing question items related to service, trading and manufacturing company material, this research succeeded in finding the advantages and disadvantages of the questions, differentiating power, reliability, group division between superior and poor, level of difficulty and quality of questions from the questions that had been prepared. The hope is that this research can provide useful guidance for educators in preparing better quality exam questions. In addition, this research can provide a solid basis for further research on developing assessment instruments that focus on competencies. The impact of the results of this research is the importance of improving the quality of exam questions so that they are more reliable and accurate in assessing student abilities. Moreover, the findings from this research can be used as a reference for improving the quality of future exam questions.